Pembelajaran Hybrid pada Pencapaian Kompetensi Pengetahuan Siswa Sekolah Dasar dalam Kurikulum Merdeka - Al-Amin, Al-Amin; Rohman, Ahmad Fadlu; Rahmat, Rahmat; Zuwardi, Zuwardi; Izmuddin, Iiz (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study discusses the effect of hybrid learning on the achievement of knowledge competencies of elementary school students within the framework of the Merdeka Curriculum. Hybrid learning, which combines online and face-to-face methods, is an alternative education needed in this digital era. This literature study reviews various literatures to identify the advantages, challenges and effectiveness of this learning model. Research reveals that hybrid learning can increase student engagement, provide flexibility in accessing materials, and encourage independent learning. However, effective implementation requires adequate technological support and teacher readiness in designing and managing learning. This finding is relevant in the context of Merdeka Curriculum, which emphasizes freedom in teaching methods to achieve optimal learning outcomes. This study recommends developing teacher competence in educational technology, as well as providing infrastructure that supports hybrid learning. Thus, it is expected that hybrid learning can improve students' understanding and skills in accordance with the demands of the modern curriculum. This research is important as a foundation for adaptive and innovative education policies in the future.